MSME Development Strategy in Central Maluku Regency - Ratih Fitriyanti Djalangkara; Erly Leiwakabessy; Maryam Sangadji; Fahrudin Ramly (PT Mattawang Mediatama Solution, 2024)
Micro, Small and Medium Enterprises (MSMEs) are one of the economic sectors that can support the regional and national economy. In addition to having a contribution to GDP, it can also absorb labor. The condition of MSMEs in Central Maluku still has various weaknesses such as capital, marketing and human resources, so there needs to be an appropriate development strategy. The purpose of this study is to determine the development strategy of MSMEs so that their contribution to the economy can be more optimal. The method used is the SWOT method which identifies various strengths, and weaknesses owned as well as opportunities and threats faced. The results showed that the right strategy to develop MSMEs in Central Maluku Regency is an aggressive strategy or growth strategy